2005
DOI: 10.1149/1.1854611
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Study of Proton-Exchange-Membrane Fuel Cell Cathode Using an Agglomerate Model

Abstract: An agglomerate model on the cathode part of the proton-exchange-membrane fuel cell is developed. A parameter estimation scheme is imposed on the model to retrieve useful mass-transfer and electrochemical kinetics data. Experimental observations on the effects of oxidant composition and solid polymer electrolyte loadings on cell performance are qualitatively predicted using this model. This model gives the trend of polarization curve as a function of gas void fraction, and loadings of catalyst and solid polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 28 publications
0
40
0
1
Order By: Relevance
“…11,12,14 Since the exact properties and thickness of the film are unknown, a resistance approach (ratio of the film thickness and permeation coefficient) is used to represent the oxygen transport resistance of the film…”
Section: Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12,14 Since the exact properties and thickness of the film are unknown, a resistance approach (ratio of the film thickness and permeation coefficient) is used to represent the oxygen transport resistance of the film…”
Section: Transportmentioning
confidence: 99%
“…Parametric studies of CLs were accomplished by Yin 14 using an agglomerate model, with the model predicting the general polarization-curve trend as a function of parameters such as gas void fraction 7,16 and ionomer 4,5,10,29 and catalyst loadings 5,10,[30][31][32] within the CL.…”
Section: _enref_29mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, recent studies have clearly shown that treating the cathode CL as an interface with uniform properties leads to several erroneous conclusions, especially due to the impact of channel-rib effects that distribute the electrons, water, heat, and oxygen unevenly at the CL boundary. [115][116][117][118] While an embedded agglomerate model is now utilized in most models, there is still an effort towards including more microstructural details.…”
Section: Catalyst-layer Modelingmentioning
confidence: 99%
“…The closest approximation to the structure is one of clumps of carbon grains (agglomerates) coated with and connected by electrolyte, [6,[10][11][12][13][14]. A widely employed approach in modelling the CCL is to assume that the agglomerates are spherical in shape, [6,7,[15][16][17][18][19][20], and to incorporate the agglomerate-level activity into a homogeneous model by assuming that a thin film of electrolyte (or water) introduces a local resistance to the oxygen-motivated by the well-established theory of porous catalysts (see Chapter 3 of [21]). The three main variants are as follows:…”
Section: Introductionmentioning
confidence: 99%